From in planta Function to Vitamin-Rich Food Crops: The ACE of Biofortification - Strobbe, Simon; De Lepeleire, Jolien; Van Der Straeten, Dominique (Frontiers in Plant Science, 2018)
Humans are highly dependent on plants to reach their dietary requirements, as plant products contribute both to energy and essential nutrients. For many decades, plant breeders have been able to gradually increase yields of several staple crops, thereby alleviating nutritional needs with varying degrees of success. However, many staple crops such as rice, wheat, and corn, although delivering sufficient calories, fail to satisfy micronutrient demands, causing the so called 'hidden hunger'. Biofortification, the process of augmenting nutritional quality of food through the use of agricultural methodologies, is a pivotal asset in the fight against micronutrient malnutrition, mainly due to vitamin and mineral deficiencies. Several technical advances have led to recent breakthroughs. Nutritional genomics has come to fruition based on marker-assisted breeding enabling rapid identification of micronutrient related quantitative trait loci (QTL) in the germplasm of interest. As a complement to these breeding techniques, metabolic engineering approaches, relying on a continuously growing fundamental knowledge of plant metabolism, are able to overcome some of the inevitable pitfalls of breeding. Alteration of micronutrient levels does also require fundamental knowledge about their role and influence on plant growth and development. This review focuses on our knowledge about provitamin A (beta-carotene), vitamin C (ascorbate) and the vitamin E group (tocochromanols). We begin by providing an overview of the functions of these vitamins in planta, followed by highlighting some of the achievements in the nutritional enhancement of food crops via conventional breeding and genetic modification, concluding with an evaluation of the need for such biofortification interventions. The review further elaborates on the vast potential of creating nutritionally enhanced crops through multi-pathway engineering and the synergistic potential of conventional breeding in combination with genetic engineering, including the impact of novel genome editing technologies.